Impact of government spending on FDI inflows: the case of ASEAN-5, China and India - Othman, Norashida; Yusop, Zulkornain; Andaman, Gul; Ismail, Mohd Mansor (Universiti Malaysia Sarawak, 2018)
This study investigates the impact of government spending towards Foreign Direct Investment (FDI) inflows in the host country using a panel data set of 7 countries spanning from 1982 until 2016. The countries of Malaysia, Indonesia, Singapore, Thailand and Philippine (ASEAN-5), India and China are utilised for the study. We examine the impact of government spending towards FDI by conducting the Pooled Mean Group (PMG) estimation developed by Pesaran et al. (1999) using market size, capital, macroeconomic stability and infrastructure as control variables. The results of this study shows that the government spending contributes positively towards FDI inflows in the long run.